INDONESIAN EFL LEARNERS AND SPEAKING ANXIETY: INSIGHTS FROM A META-SYNTHETIC ANALYSIS - Mustamir, Mustamir (University of Kuningan, 2024)
This study presents a comprehensive meta-synthetic analysis of speaking anxiety among Indonesian English as a Foreign Language (EFL) learners. Speaking anxiety is a common challenge that significantly impacts the language acquisition process, affecting learners' confidence, performance, and overall proficiency. The meta-synthesis method was employed to integrate and interpret findings from multiple qualitative and quantitative studies conducted in the Indonesian context. The analysis reveals several key factors contributing to speaking anxiety, including fear of negative evaluation, lack of confidence in language proficiency, and cultural influences on communication styles. Additionally, the study highlights the role of educational environments and teacher-student dynamics in exacerbating or alleviating anxiety. The findings suggest that targeted interventions, such as supportive teaching practices, anxiety-reducing classroom activities, and the development of a positive learning environment, can effectively mitigate speaking anxiety. This meta-synthesis provides valuable insights for educators, policymakers, and researchers aiming to enhance EFL education in Indonesia by addressing the psychological barriers to effective language learning. By synthesizing diverse perspectives and empirical evidence, this study contributes to a deeper understanding of speaking anxiety in the Indonesian EFL context and offers practical recommendations for fostering a more conducive learning atmosphere for language learners.